Anthrax in wartime Ukraine requires increased surveillance - Joel Keep; David James Heslop (University of New South Wales, 2023)
This Watching Brief provides analysis of a recent outbreak of anthrax amongst goats in Ukraine. Occurring outside the usual expected geography, this cluster is an illustration of the challenges facing Ukrainian authorities in maintaining disease surveillance during wartime. The context of the ongoing Russian invasion of the country should alert local authorities and international donors to the importance of discerning between bacteriological outbreaks of natural and unnatural cause, especially given the potential for battlefield use of unconventional weapons as the conflict escalates.